Young Generation Perception on Sri Lankan Refugees and Their Representation in Tamil Films - Mezsia, John (Journal of Advanced Research in Journalism & Mass Communication, 2023)
This article investigates the role of representation in Tamil films as to how the Sri Lankan refugees are portrayed in films and further it studies to understand the life of Sri Lankan refugees in Indian Refugee camps and the reality that are represented in films. It further helps us understand the impact of representation theory in films and the role and art of how it is used to convey various types of stories in Cinema. The researcher particularly taken three movies that were top ranked in the pilot study, ‘Nandha’ (2001) by director ‘Bala, Kannathil Muthamital’ (2002) by director Mani Ratnam and ‘Jagame Thanthiram’ (2021) by director Karthik Subbaraj to understand the Sri Lankans portrayals. This investigation is essential to understand as to what kind of re-presentations the film makers in Tamil Cinema are trying to send across. Tamil filmmakers in India frequently depict Sri Lankan refugees in their films. They represent the Sri Lankan refugees in a variety of ways, including via characters, scenery, attire, education, livelihood, trading, employability. They portray them in a variety of roles too. The results of this study will help the researcher to understand how this marginalized community has been used in the film. How to cite this article: Mezsia J. Young Generation Perception on Sri Lankan Refugees and Their Representation in Tamil Films. J Adv Res Jrnl Mass Comm 2023; 10(1): 33-38. DOI: https://doi.org/10.24321/2395.3810.202307